Socioeconomic Inequities in Preemptive Kidney Transplantation and Graft Survival: An Innovative Approach to Identifying Disparities in Kidney Transplantation - Sarah Kizilbash, MD; Chung-II Wi, MD; Madison Roy, MS; Euijung Ryu, PhD; Arthur Matas, MD; Vesna Garovic, MD, PhD; Samy Riad, MD, MS; Carrie Schinstock, MD; Young Juhn, MD (Transplantation Direct)
Background. The limitations of conventional measures of socioeconomic status (SES) limit our ability to elucidate the role of SES as a key element of social determinants of health in kidney transplantation. This study’s objective was to use an innovative SES measure, the HOUsing-based SES measure (HOUSES) index, to examine the effects of social determinants of health on access to and outcomes of kidney transplantation. Methods. Our study included residents of Minnesota (age older than 18 y) who underwent kidney transplantation at a single center between 2010 and 2020. SES was determined using the HOUSES index, categorized into quartiles (Q1 for lower, Q2–Q4 for higher SES). We used mixed-effects multivariable logistic and Cox models to examine the effects of HOUSES on preemptive transplants, pretransplant dialysis duration, and death-censored graft loss, adjusting for covariates. Results. Among 1975 eligible patients, 29.4% received preemptive transplants, 34.9% underwent pretransplant dialysis for >3 y, and 15.1% experienced death-censored graft loss for a median follow-up of 7.15 (interquartile range, 4.25–11.38) y. Lower SES recipients (Q1) demonstrated decreased preemptive transplant likelihood (adjusted odds ratio [aOR]: 0.74; 95% confidence interval [CI], 0.57-0.97; P = 0.03), longer dialysis duration (>3 y; aOR: 1.43; 95% CI, 1.01-2.03; P = 0.046), and higher death-censored graft loss (adjusted hazard ratio 1.36; 95% CI, 1.02-1.12; P = 0.036) versus higher SES recipients (Q2–Q4). Conclusions. We observed significant socioeconomic disparities in kidney transplant access, dialysis duration, and graft survival. The HOUSES index may be a promising tool for individual-based targeted interventions as it identifies SES on an individual rather than an area-level basis.